"Taphonomy: Dead and fossilized": A new board game designed to teach college undergraduate students about the process of fossilization. Issue 3 (2nd July 2020) - Martindale, Rowan C.; Weiss, Anna M.
Abstract: Incorporating games in teaching can help students retain material and become innovative problem solvers through engagement and enjoyment. Here we describe a new board game, "Taphonomy: Dead and Fossilized, " and its use as an active learning tool (material available at doi: 10.18738/T8/NQV2CU). The educational objective is to teach the player about taphonomy and fossilization, while the gameplay objective is to preserve and recover the best fossil collection. Through competitive gameplay, students learn how chemical, physical, and environmental factors, as well as physiology and discovery biases can influence an organism's preservation and collection potential. The game is modeled after an Early Jurassic fossil deposit for scientific accuracy and relevance. The game was incorporated in undergraduate classroom activities in 20 colleges and universities across the United States. Survey results show that students and teachers were overwhelmingly positive about the game, stating that it was fun and helped them learn or strengthen their knowledge of fossilization. When analyzed statistically, we find that students' self-reported learning outcomes and opinions vary most significantly with college year, major, ethnicity, and race. White students and geoscience or STEM majors reported the highest levels of learning and enjoyment, with minorities and non-STEM majors responding less favorably. We suggest this game is most advantageous for use in upper-level paleontology classrooms, although it is still beneficial at lower levels. It is critical to use this game as part of a larger lesson plan and tailor it to fit the needs of an individual classroom. Modifications for time and class size, as well as follow-up discussion questions, are included.